Relationships of waving rate, waving length, and swimming velocity in the 50 m surface - Comparison of the finalists and the non-finalists in the world championships of Finswimming - Oshita, K.; Ross, M.; Koizumi, K.; Yano, S.; Kashimoto, S.; Takahashi, K.; Kawakami, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2008)
The aim of present study was to quantify the Waving techniques, such as Waving rate (WR; Waving per second), Waving length (WL; distance per Waving), and swimming time (ST), in the finalists and the non-finalists in Finswimming world championships in the 50 m Surface. The subjects were 5 finalist males and 5 non- finalist males in 12th Finswimming world championships in the 50 m Surface. ST of the finalists was faster than that of the non-finalists (16.37 sec vs. 17.91 sec, P < 0.01), and WL of the finalists was longer than that of the non- finalists (1.16 vs. 1.06 meter, P < 0.05). There was no significant difference between the finalists and the non- finalists with regard to WR (2.65 vs. 2.64 Hz). There was a significant negative relationship between ST and WL (r = -0.88, P < 0.01). However, there was no significant relationship between ST and WR (r = 0.32, P = 0.38). Furthermore, WR was a significantly correlated with the residual error of ST, calculated from the regression analysis for the relationship between WL and ST (r = -0.67, P = 0.03). These results suggest that WL is concluded to be an important factor that influences ST for elite athlete in the 50 m SF.